2022
DOI: 10.3390/cells11213352
|View full text |Cite
|
Sign up to set email alerts
|

Role of mGlu5 in Persistent Forms of Hippocampal Synaptic Plasticity and the Encoding of Spatial Experience

Abstract: The metabotropic glutamate (mGlu) receptor family consists of group I receptors (mGlu1 and mGlu5) that are positively coupled to phospholipase-C and group II (mGlu2 and mGlu3) and III receptors (mGlu4-8) that are negatively coupled to adenylyl cyclase. Of these, mGlu5 has emerged as a key factor in the induction and maintenance of persistent (> 24 h) forms of hippocampal synaptic plasticity. Studies in freely behaving rodents have revealed that mGlu5 plays a pivotal role in the stabilisation of hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 242 publications
0
8
0
Order By: Relevance
“…The maintenance of later phases of LTP beginning at around 90 min post-induction, are supported by phospholipase -C coupled (group 1) receptors ( Hagena and Manahan-Vaughan, 2022 ; Mukherjee and Manahan-Vaughan, 2023 ). Group 1 mGlu receptors can functionally interact with NMDAR and alter NMDAR currents ( Rosenbrock et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of later phases of LTP beginning at around 90 min post-induction, are supported by phospholipase -C coupled (group 1) receptors ( Hagena and Manahan-Vaughan, 2022 ; Mukherjee and Manahan-Vaughan, 2023 ). Group 1 mGlu receptors can functionally interact with NMDAR and alter NMDAR currents ( Rosenbrock et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal information processing is highly state-dependent, and effects are reflected by changes in the coupling of neuronal oscillations at theta-gamma frequencies [101]. In freely moving rats, identical afferent stimulation frequencies can result in robust LTP, STP, or no change in synaptic efficacy in the absence of any overt change in behaviour, although changes in the coupling of theta-and gamma-frequency neuronal oscillations during the stimulation predict the plasticity outcome [15]. Furthermore, stress changes the thresholds for the induction and maintenance of synaptic plasticity [102][103][104], as can alterations of the action of neuromodulators in the hippocampus [105].…”
Section: Synaptic Plasticity Is Not the Only Change In Synaptic Effic...mentioning
confidence: 99%
“…Studies of the molecular basis of persistent (>24 h) LTP, for example, in the cornu ammonis-1 (CA1) region in vivo have revealed that it can be disambiguated into temporal components comprising STP that requires activation of N -methyl- d -aspartate receptors (NMDAR) and lasts for 30–90 min, depending on the subunit composition of the NMDAR [14]. This early phase of LTP then segues into LTP that lasts for 90–180 min in behaving rodents and requires activation of the metabotropic glutamate receptor, mGlu5 [15]. LTP that lasts for more than 3 h requires brain-derived neurotrophic factor (BDNF) [16], whereas CA1 LTP that lasts for longer than 8 h (referred to as late-LTP) requires both protein translation and transcription [17].…”
Section: Temporal Phases Of Hippocampal Synaptic Plasticitymentioning
confidence: 99%
See 2 more Smart Citations